Journal of Outdoor and Environmental Education - Quay, John.; Gray, Tonia; Thomas, Glyn.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The Journal of Outdoor and Environmental Education (JOEE) is a double-blind peer-refereed journal devoted to the scholarly examination of issues in outdoor and environmental education. JOEE provides a forum in which outdoor and environmental education professionals from all settings can exchange and discuss ideas and practices relevant to their work. JOEE invites submissions of papers of between 4000 and 8000 words (including reference list and abstract) that focus on enhancing understanding of outdoor and environmental education issues through balanced and in-depth investigation of practices and theories relevant to outdoor and environmental education. JOEE does not privilege any particular methodology or theory and welcomes contributions from various standpoints. However, editorial will prioritise papers that take into consideration a broad readership which includes teachers and other practitioners as well as researchers, requiring authors to express and explain evidence and theory using language that is accessible to readers beyond a particular community.
Keywords: Curriculums (Courses of study).; Education -- Curricula; Educational sociology; Environmental and Sustainability Education; Curriculum Studies; Sociology of Education